2017
DOI: 10.1038/s41467-017-01458-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing by ADAR1 leads to context-dependent transcriptome-wide changes in RNA secondary structure

Abstract: Adenosine deaminase acting on RNA 1 (ADAR1) is the master RNA editor, catalyzing the deamination of adenosine to inosine. RNA editing is vital for preventing abnormal activation of cytosolic nucleic acid sensing pathways by self-double-stranded RNAs. Here we determine, by parallel analysis of RNA secondary structure sequencing (PARS-seq), the global RNA secondary structure changes in ADAR1 deficient cells. Surprisingly, ADAR1 silencing resulted in a lower global double-stranded to single-stranded RNA ratio, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 78 publications
7
99
0
Order By: Relevance
“…Moreover, in the RNase protection assay described above, wild-type MDA5 protects IR- Alu RNAs amongst total RNA extracted from ADAR1-deficient cells, but not amongst RNA from wild-type cells [25]. Together with the MDA5-dependency of type I IFN induction in ADAR1-deficient mice and cells 85, 86, 87, these data suggest an attractive model: ADAR1 edits RNAs derived from IR- Alu repeats, leading to destabilization of their base-paired structure, which in turn prevents activation of MDA5 25, 96. This model is further consistent with the notion that IFIH1 mutations found in AGS change the RNA specificity of MDA5 such that it binds to IR- Alu elements containing mismatches and bulges [25].…”
Section: Activation Of Mda5 In Autoimmune and Autoinflammatory Diseasesmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, in the RNase protection assay described above, wild-type MDA5 protects IR- Alu RNAs amongst total RNA extracted from ADAR1-deficient cells, but not amongst RNA from wild-type cells [25]. Together with the MDA5-dependency of type I IFN induction in ADAR1-deficient mice and cells 85, 86, 87, these data suggest an attractive model: ADAR1 edits RNAs derived from IR- Alu repeats, leading to destabilization of their base-paired structure, which in turn prevents activation of MDA5 25, 96. This model is further consistent with the notion that IFIH1 mutations found in AGS change the RNA specificity of MDA5 such that it binds to IR- Alu elements containing mismatches and bulges [25].…”
Section: Activation Of Mda5 In Autoimmune and Autoinflammatory Diseasesmentioning
confidence: 92%
“…recently reported that adenosines edited by ADAR1 tend to be found in single-stranded, rather than base-paired, regions of both single Alu and IR- Alu elements [85]. Moreover, A-to-I editing can in some circumstances stabilise RNA duplexes formed by Alu elements [96] and inosine-containing RNAs may in some settings inhibit RLRs [97]. Finally, RNAs derived from IR- Alu elements are bound by additional proteins such as DHX9 [98], which may compete with ADAR1 and MDA5.…”
Section: Activation Of Mda5 In Autoimmune and Autoinflammatory Diseasesmentioning
confidence: 99%
“…The edits made by ADAR in codons alter protein sequence since inosine is translated as guanosine, while those modifying splice sites and untranslated regions (UTR) change the isoform mix and transcript stability. Editing of miRNA dsRNA precursors also occurs and alters expression of miRNAs and the genes that they regulate 34 . Altering an A:C mismatch to an I:C basepair favors dsRNA formation, while editing of an A:U basepair to I:U is destabilizing 34 .…”
Section: Adar and Dsrnamentioning
confidence: 99%
“…Editing of miRNA dsRNA precursors also occurs and alters expression of miRNAs and the genes that they regulate 34 . Altering an A:C mismatch to an I:C basepair favors dsRNA formation, while editing of an A:U basepair to I:U is destabilizing 34 .…”
Section: Adar and Dsrnamentioning
confidence: 99%
“…Inosine is interpreted as guanosine upon translation or sequencing, meaning A-to-I editing leads to post-transcriptional Ato-G transitions in RNA. Editing occurs within regions of double-stranded RNA (dsRNA), and inosine has different thermodynamic base pairing properties to adenosine, harboring the potential to alter both the RNA code and the secondary structure [5][6][7][8]. A-to-I editing levels vary across transcripts, tissues, and throughout development ranging from < 1 to 100% at any given site [4,9].…”
Section: Introductionmentioning
confidence: 99%